Microwave – Assisted Extraction (MAE) Of Rhizome Kaempferia Parviflora Crude And Its Biological Activity - Mohammad Gial, Mohamad Anwar (Universiti Sains Malaysia, 2021)
Extraction is a process to separate the desired natural products from the raw materials. It has been used in various industry such as food and pharmaceutical industries to achieve certain level of nutrients in the products. However, traditional extraction method required a large volume of solvents and longer extraction time. Hence, advanced extraction which is microwave-assisted extraction was carried out. This research study focusses on green extraction technique where the solvent used is water. Microwave-assisted extraction (MAE) was optimized by Response Surface Methodology (RSM) to enhance the extraction of rhizome K. Parviflora crude. The optimization was done to get the optimum microwave power, microwave extraction time and solvent to feed ratio with maximum response. Central Composite Design (CCD) was selected as a model for RSM to evaluate the first and second-order polynomial model. The analysis of variance was used to evaluate the model fitness and optimal condition. Considering the maximum content of extracted yield, total phenolic content and antioxidant activity, the optimal conditions for all investigated response were obtained at microwave power of 360 W, microwave time of 2 min and solvent feed ratio of (10:1). Under the optimal condition, obtained K. Parviflora crude extract contained 16.72% yield of crude extract, 18.24 μg /ml of total phenolic content and 142.681 μg/ml of antioxidant activity. The study revealed that the response surface methodology (RSM) is an efficient statistical method for preparing appropriate empirical model related to the independent variables and predicting the optimum conditions influencing K. Parviflora crude extract. Microwave-assisted extraction is an environmental-friendly technique for extractions of bioactive compounds and an attractive alternative procedure in industry food and traditional herb.